The effectiveness of pedestrian bridge - Nada Nadhirah, Abdul Latif (2017)
Road accident is one of the major cause of death and injuries in Malaysia. Nowadays, the world faces the big challenge of traffic accidents that collect annually millions of human lives. From the traffic accidents, it not only affects the victim but also give impact to the community and its progress. There is large great way to vehicles moving through the area. Crossing the wide road and a speeding vehicle, it can be a dangerous to pedestrians and bikers who want to cross the road. Built the pedestrian bridge at some the area especially in the urban area can help pedestrian and cyclists to safely cross a busy road without conflict. However, the pedestrian bridge that has been built is not fully used by pedestrians and be waste. The pedestrians more prefer to cross the road without using the pedestrian bridge. Therefore, the objectives of this study are to identify the reason for compliance and non – compliance of pedestrian bridge as well to identify the method to improve the pedestrian bridge usage in Pekan Pahang. From the research, the total number of pedestrian that use for both location is 67 and the number of motorcycle that use the motorcycle bridge for both location is 69. Most of pedestrian at Taman Sri Inderapura will use the pedestrian bridge especially at during peak hours which is at 7 – 9 am, 12 – 1 pm and during end of office hour. Has some suggestion that can improve the use of this pedestrian bridge such as upgrade the facilities of the pedestrian such as fixed the lighting, paint the barriers to attract the pedestrian use it and also make the escalator to make them easier. Next, make a better design such as a new shape, material and dimension. Make a big dimension for the road space. Then, make a huge drain next to the pedestrian and make a cascade shape for the motorcycle route.